Guest editorial: Educational design research for digital learning technologies to promote inclusion, equity, and accessibility - Ge, Xun; Liu, Juhong Christie; Li, Zhe (Educational Technology ＆ Society, 2024)
This collection of 12 papers reflects the evolving research methods at different design and development stages of educational design research (EDR). With the theme of investigating human-cantered digital technologies serving inclusion, equity, and accessibility, the researchers conducted EDR to solve real-world problems and promote learning access. These research studies ranged from needs analysis, learner/user experience, prototype design and development, to implementation and evaluation. The empirical data or evidence at various testing phases of these studies extended the dimensions of EDR and informed intentional investment in digital technology and related research to build a more inclusion- and equity-driven learning environment.